Milk peptides: effect on enzymatic hydrolysis of sodium caseinate - Haque, Zahur U.; Antila, Pirkko (Agricultural Research Centre of Finland, 1993)
Tutkimuksessa hydrolysoitiin natriumkaseinaatti (NACN) Rhozyme41:llä (Rh41), Neutrasilla (Neu) ja plasmiinilla (PL), jolloin saatiin seuraavat peptidiyhdisteet: Na-Cas-P-Rh41, Na-Cas-P-Neu ja Na-Cas-P-PL. Alkuperäiset herapeptidit (indigenous whey proteins = IWP) saatiin tuoreesta herasta saostusmenetelmällä. Näitä peptidifraktioita käytettiin tutkittaessa maidon peptidien vaikutusta eräiden proteaasien aktiivisuuksiin. Kaikki tutkitut peptidifraktiot alensivat entsyymiaktiivisuuksia. Na-Cas-P-Rh41 oli voimakkain entsyymiaktiivisuuden heikentäjä, sillä se alensi trypsiini-, Rh41-, Neu- ja PL-aktiivisuuksia 15, 32, 50 ja 14 %. IWP alensi selvästi Rh41-aktiivisuutta. Heran ultrasuodatus-konsentraatiotaso oli suoraan verrannollinen entsyymi-inhibition voimakkuuteen.

Sodium caseinate (NaCN) was hydrolyzed using Rhozyme 41 (Rh41), Neutrase (Neu) and plasmin (PL) to obtain peptide preparations termed; Na-Cas-P-Rh41, Na-Cas-PNeu, and Na-Cas-P-Plasmin, respectively. Indigenous whey peptides (IWP) were obtained from fresh sweet whey, at different levels of ufconcentration, by a precipitation method described earlier. These peptide fractions were then used to observe their effect on the activity of some proteases. All peptide preparations depressed enzyme activity. Na-Cas-P-Rh41 was the most powerful inhibitor of enzyme activity and decreased the activity of trypsin, Rh41, Neu, and PL by 15, 32, 50, and 14%, respectively. IWP markedly depressed activity of Rh41. The degree of uf-concentration of whey from which IWP was obtained was directly related to degree of inhibition.
Keywords: Re; peptidit; maito; juustot; entsyymit; peptide; casein; cheese; ripening; enzyme